Impacto socioeconômico da implantação da Fundação Universidade Federal do Pampa – UNIPAMPA - Pahim, Frank Sammer Beulck (2018)
This research seeks to analyze the socioeconomic impacts resulting from the implementation of UNIPAMPA in the West and South regions of Rio Grande do Sul. The Ministry of Education and Culture (MEC) programs for internalization and expansion of higher education and Restructuring and Expansion of Federal Universities REUNI), carried out from 2003 to 2012, increased the number of municipalities served by public universities. These public policies aimed at reducing regional asymmetries, as well as the expansion of vacancies and democratization of access to public higher education, based on the performance of the new universities. Universities constitute engines for development based on their role in teaching, research and extension, in interaction with other social agents. Identifying the impacts resulting from the implementation of a new university constitutes social interest and the general objective of the research, as well as to define adequate indicators, referenced in the literature and with data availability to demonstrate the effects of the policy and the scope of its purpose. The definition of the indicators and the comparison of the performance of the cities that received the campus were great challenges to the research, given the social, cultural and economic differences existing between regions of the state. The solution found for comparing the performance in the indicators was the use of the economic classification of cities in the National Policy of Regional Development I and the comparison with the performance at the state level. The data were mostly collected on statistical bases recognized or obtained directly from the public agencies in charge of the information. The methodology to reach the objectives used the analysis of the geographic insertion, the institutional investments, the performance of the indicators and of parametric and nonparametric statistical tests, with the aid of the software Statistical Package for Social Sciences (SPSS), to identify the impact of higher education in the socioeconomic development of the regions. The contextualization of the geographical insertion of UNIPAMPA showed that its socioeconomic impact is diluted in regional development by its multicampi performance, leveling microregions where there are cities with historical development differences and helping to reconfigure the regional hierarchy. The information set made it possible to conclude that UNIPAMPA has a greater or lesser impact on all the indicators analyzed, such as, for example, the inversion of negative population trends, the unemployment rate, the reduction of income concentration or the improvement of quality of life, measured by the HDI. The statistical tests of mean and median difference showed that the group of cities with UNIPAMPA presents similar performance to the group formed by the Comparison Units (UC) in several indicators, noting that in the CU there are cities that are regional poles with a better historical economic performance in the individual comparison, and the temporality of the data obtained in relation to the short time of existence of the university.